Soluble guanylyl cyclase, the NO receptor, drives vasorelaxation via endothelial S-nitrosation - Waqas Younis; Pia C. Burboa; Tanaz Sadeghian; Veronica Kuzdowicz; Chuanlong Cui; Ping Shu; Yong Qin; Lai-Hua Xie; Mauricio A. Lillo; Annie Beuve (Proceedings of the National Academy of Sciences, 2025)
We previously demonstrated that the NO-stimulated soluble guanylyl cyclase (GC1), which produces cGMP, also has the ability to transfer S-nitrosothiols (SNO) to other proteins in a reaction involving oxidized Thioredoxin 1 (oTrx1). This transnitrosation cascade was established in vitro and involved Cys 610 (C610) of GC1 as the major SNO-donor. To assay the relevance of GC1 transnitrosation under physiological conditions and in oxidative pathologies, we studied a knock-in mouse in which C610 was replaced with a serine (KI αC 610S ) under basal or angiotensin II (Ang II)-treated conditions. Despite similar GC1 expression and NO responsiveness, the Ang II-treated KI mice displayed exacerbated oxidative pathologies including higher mean arterial pressure and more severe cardiac dysfunctions compared to the Ang II-treated WT. These phenotypes were associated with a drastic decrease in global S-nitrosation and in levels of SNO-Trx1 in the KI mice. To investigate the mechanism underlying the dysregulation of blood pressure, pressure myography and in vivo intravital microscopy were conducted to analyze the vascular tone of resistance vessels. Both approaches indicated that, even in the absence of oxidative stress, the single mutation C610S led to a significant disruption of the endothelium-dependent, acetylcholine-induced vasorelaxation while NO-dependent smooth muscle relaxation remained unchanged. Mechanistically, the vasorelaxation defect was associated with decreased endothelial calcium influx and membrane hyperpolarization, independent of NO bioavailability. These findings indicate that the C610S mutation uncouples two NO signaling vasodilatory pathways (endothelial SNO and smooth muscle NO-cGMP) and suggest that GC1 transnitrosation activity is essential for endothelium-derived hyperpolarization.